The Meaning of God In Deutronomy 6:6-9 and Its Implication Today - Yeremia Yeremia; Jhon Wesley (Syntax Corporation, 2022)
The book of Deuteronomy is a book that contains the confirmation of God's promise to the Israelites by the elders of the nation of Israel. This book contains the remembrance made by Moses to the new generation of the Israelites, who at that time did not exist and were not present when God first conveyed His promise of a land flowing with milk and honey, and God's inclusion in the nation of Israel. So that in this book the words and promises of God are repeated and uttered, in addition to reminding and strengthening the faith of the new generation of Israel, but also to warn this new generation of God's commands and prohibitions, what is worthy and despised for those in the world. his eyes. The author explains the meaning of the words in Deuteronomy 6:6-9, describes the message and mandate contained in these verses and passages and interprets God's message in Deuteronomy 6:6-9. The methods used in this exegesis include historical studies, lexical studies, and grammatical studies. And then compared to the results of the interpretation of the experts. The results of this writing are obtained: Why did God convey this message to the Israelites at that time? What did God want to mean by sending Moses to repeat the preaching of God's promises and His commandments to the new generation of the Israelites? And what is the current implementation?. Keywords: concept of god; deutronomy 6:6-9; implication